Implementation of lean manufacturing to increase the machine’s availability of a metalworking company - Cabezas Fulca, Diego Jesús (2023)
The main objective of Lean Manufacturing tools is to eliminate waste from a process in order to make it more efficient. In this applied research with a quantitative approach, the production process of a steel coil cutting machine (Slitter) of a Peruvian metalworking company is analyzed. It can be said that the Slitter is indispensable to supply semi-finished products to a steel tube production line. Likewise, improvements are proposed and implemented based on three lean manufacturing tools in order to increase their availability, which hardly exceeds the value of 60%. One of the tools implemented was the single minute exchange of die (SMED), which is aimed at reducing machine preparation times (setup) by reorganizing internal to external activities. Another tool used was Kaizen, which seeks continuous improvement and standardization of processes through simple and concrete actions. Finally, the 5s method was applied to improve the cleanliness and order of the work areas. After these, the time available to produce increased 95.73 hours per month, which means an improvement of 17.36% in machine availability. Also, setup times and operation cycle times were reduced by 16% and 16.35% respectively.